A REVIEW ON A FEW LEGUMES AND METHODS OF PROTEIN QUANTITATION (International Association of Biologicals and Computational Digest, 2023)
Leguminosae (Fabaceae or Papilionaceae) is one of the largest angiospermic families. Consisting of several important plants which are also called as legumes, leguminosae is the third largest plant family. This review presents a report on a few select legumes such as Cicer arietinum (Chick pea), Medicago sativa (Alfa alfa), Vigna mungo (Black gram), and Pisum sativum (Pea). The essentiality of protein contents of the select legumes has been highlighted. There are several methods stated for the protein quantitation such as Biuret, Kjendahl, Bradford, Lowry, Smith, Warburg-Christian, etc. The most recommended and majorly employed protein analysis methods are of Bradford (1976) and Lowry’s (1951).
Keywords: Leguminosae; Cicer arietinum; Medicago sativa; Vigna mungo; Pisum sativum; Protein analysis; Bradford; Lowry